1975
DOI: 10.1136/pgmj.51.597.471
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypocalcaemia on glucose tolerance, insulin release and free fatty acid levels in human subjects

Abstract: SummaryEight patients with hypocalcaemia who presented with frank or latent tetany due to parathyroid insufficiency or nutritional osteomalacia were studied. Their serum calcium ranged from 6'85 to 7 7 mg/100 ml (mean 7-33±0-36 mg/100 ml). In six of them, serum calcium after treatment varied from 8 4 to 9-2 mg/100 ml. In ten healthy normal subjects the serum calcium levels were 9 0-10'2 mg/100 ml (9'50±0 47 mg/100 ml). The blood glucose levels during a 3 hr oral GTT were significantly elevated during hypocalca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

1977
1977
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…It has been suggested that disorders which increase in prevalence with increasing latitude, and present more commonly in winter, such as ischaemic heart disease, could prove to relate to vitamin D deficiency [30]. This suggestion is supported by the reductions in NEFA concentrations [9,21] and in insulin resistance [9] reported with correction of vitamin D depletion in man, to which secondary hyperparathyroidism has been suggested to contribute [31]. Examination of dietary information from the survey of which the present study is a part has shown initial serum 25-hydroxy-vitamin D concentrations in at-risk subjects at OGTT to be related to the consumption of fish; a relationship found in both at-risk and not-at-risk subjects (p < 0.04 and < 0.02, respectively) [14].…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…It has been suggested that disorders which increase in prevalence with increasing latitude, and present more commonly in winter, such as ischaemic heart disease, could prove to relate to vitamin D deficiency [30]. This suggestion is supported by the reductions in NEFA concentrations [9,21] and in insulin resistance [9] reported with correction of vitamin D depletion in man, to which secondary hyperparathyroidism has been suggested to contribute [31]. Examination of dietary information from the survey of which the present study is a part has shown initial serum 25-hydroxy-vitamin D concentrations in at-risk subjects at OGTT to be related to the consumption of fish; a relationship found in both at-risk and not-at-risk subjects (p < 0.04 and < 0.02, respectively) [14].…”
Section: Discussionsupporting
confidence: 65%
“…It is possible, therefore, that longterm vitamin D depletion could contribute to the increased prevalence of diabetes seen in Asians migrating to Northern Europe as compared to that of indigenous Caucasians. Early correction of vitamin D depletion has been shown to restore both insulin secretion and normoglycaemia in dialysis patients developing glucose intolerance with failing 1-hydroxylation of 25-hydroxy-vitamin D [6,23] and in earlier case reports of treatment of vitamin D deficiency in subjects with glucose intolerance [9]. As in previous reports of treatment with vitamin D or its active di-hydroxy form in four vitamin D-depleted patients with established diabetes [17], and in 35 patients with NIDDM [24], we found no improvement in abnormal glucose tolerance in our 22 vitamin D-treated subjects despite improvement in insulin output.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of a sufficient amount of extracellular calcium is required for glucose to stimulate insulin secretion in the pancreatic beta cell (Grodsky & Bennett 1966;Milner & Hales 1967;Curry et al 1968;Malaisse et al 1970;Charles et al 1975;Malaisse 1972;Hellmann 1975;Witzel & Littledike 1973;Littledike et al 1968). It has been demonstrated by Gedik & Zileli (1977) and other investigators (Bansal et al 1975;Laron & Rosenberg 1970;Yasuda et al 1975) that in the hypocalcaemic state, insulin secretion and glucose tolerance are reversibly impaired in human beings.…”
mentioning
confidence: 92%